Associations of Personality, Political Skill and Emotional Intelligence with Emotion Work (Global Journal of Human-Social Science, 2014)
In customer service occupations, emotional control plays a crucial role in client interface. Employees in these occupations require skilful handling of customer related issues. This demands adequate control of clients' feelings and emotions. A blend of qualities in employees persuades them to respond to the clients. Thus, the degree of emotional stability that employees have strongly influences their inner self. By using cross sectional descriptive survey on 200 customer service workers across the country, the study examines the associations of personality, political skill and emotional intelligence with emotion work. The subjects were assessed on emotion work, personality, emotional intelligence, and political skill. Pearson correlation and hierarchical multiple regression were used to analyze the data. Results revealed that personality, political skill and emotional intelligence emerged as strong predictors of emotion work. This study highlights the need for understanding emotion work as an important potential interpersonal variable for enhancing employees' as well as organizational health.
Keywords: emotion work; personality; political skill; emotional intelligence